2022
DOI: 10.32517/0234-0453-2022-37-3-80-87
|View full text |Cite
|
Sign up to set email alerts
|

Project-based learning approach to the formation of digital competencies of students of universities in Russia and India

Abstract: Modern challenges in society require universities to move from a traditional to a competency-based technology integrated learning environment. Students must master a variety of newer complex competencies such as: learn to independently search for information, analyze it, and apply it to solve various real time problems through their content knowledge. One of the possible tools for developing these newer competencies is ICT integrated project-based learning (PBL). The present study conducts an ICT integrated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The list of participants in business processes is determined, who in the future will be users of the database; a conceptual and logical model of the database is being developed, the normalization process is being carried out; the database is implemented at the physical level and the client application is developed. Students "open their eyes", they begin to understand how information systems are designed and created for a real specific task, which undoubtedly motivates them to master the profession [8,9].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The list of participants in business processes is determined, who in the future will be users of the database; a conceptual and logical model of the database is being developed, the normalization process is being carried out; the database is implemented at the physical level and the client application is developed. Students "open their eyes", they begin to understand how information systems are designed and created for a real specific task, which undoubtedly motivates them to master the profession [8,9].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…et al (2021), in the year of the work they have done that is presented to the students in a project-based practical education in teaching courses, intended to inform the experiences of projects, and their work is shaped accordingly, as a result of the research project-based teaching, training opportunities, motivation and modelling of the participants showed a positive attitude towards education and research, it is observed that this model achieves results better with expressing themselves. Lapina and Prakasha (2022), in the work they have done in the year students in project-based education, expressed that they were conducting integrated application and application for a joint work sought to uncover a common theme, and as a result, project organisation, technology tools and such of the requirements for a design to implement projects that provide benefits and achieves results, it is observed that the proposed year. Orlova and Firsova (2022) brought literature in the digital transformation of the education system to create a new model in studies of students' communicative competence in the formation of Project-Based Learning has attempted to address some aspects of the application and, as a result, project work, digital educational environment in the educational process to enhance motivation for learning and achieving results necessary in educational communication technology that allows the modelling of becoming a learning achieves results that are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Project‐Based Learning adoption and implementation for different groups and contexts, especially cross‐national studies are understudied (Chen & Yang, 2019; Hasni et al., 2016). Most Indian studies on PBL focus on higher education (Kulshreshtha et al., 2022; Lapina & Prakasha, 2022; Taneja, 2022). The limited studies on PBL in Indian schools have primarily been on Maker Projects or engineering design.…”
mentioning
confidence: 99%